New Insights Into the Development of the Anterior Abdominal Wall - Bouzada, Jose; Gemmell, Carolina; Konschake, Marko; Tubbs, R. S.; Pechriggl, Elisabeth; Sañudo, Jose (Frontiers in Surgery, 2022)
Purpose Among the few studies that have examined the development of the anterior abdominal wall, several are based on incomplete “series”, substituted in many cases by non-human specimens. Material and Methods In total, 19 human embryos corresponding to Carnegie stages 15–23, 36 fetuses with estimated gestational ages ranging from 9 weeks to term, and eight neonates were included in this study. All specimens belong to the collection of the Department of Anatomy and Embryology at the Complutense University of Madrid. Results The muscles of the anterior abdominal wall appear in the dorsal region at stages 15 and 16 (33–37 days). At stages 17 and 18 (41–44 days), this muscular mass grows ventrally and splits into two sheets: the external abdominal oblique muscle and the common mass of the internal abdominal oblique, and the transversus abdominis muscles, all of which end ventrally in the primitive condensation of the rectus abdominis. In embryos at stages 19 and 20 (48 days), the anterior abdominal wall continues to show an umbilical hernia in the amniotic cavity. However, a narrow neck is apparent for the first time and there is a wider anterior abdominal wall below the hernia made up of dense mesenchyme tissue without layers and showing the primordia of the umbilical canal. In embryos at stages 21, 22, and 23 (51–57 days), the abdominal muscles and aponeuroses cross the midline (linea alba) covering the rectus abdominis and pyramidalis muscles while the umbilical hernia has shrunk. In fetuses during the 9th and 10th weeks, the umbilical hernia becomes encircled by the rectus abdominis muscle, its aponeurosis, and the three layers of lateral abdominal muscles, which are more developed and covered by Camper's and Scarpa's fasciae. The inguinal canal has a course and relationships like those described in adults, with Hesselbach's ligament.